The Study of Biocontrol Effect of Trichoderma harzianum against Colletotrichum, Corynespora, Fusarium graminearum and Fusarium napiforme: A Comprehensive Analysis (International Journal of Food and Nutritional Sciences, 2022)
Trichoderma harzianum, a ubiquitous filamentous fungus, has gained significant attention as a potent biocontrol agent against various phytopathogens. The present research is a comprehensive study on the biocontrol effect of Trichoderma harzianum against four important plant pathogens, namely Colletotrichum, Corynespora, Fusarium graminearum, and Fusarium napiforme isolated from Luffa acutangula (ridge gourd) and Citrullus lanatus (watermelon) by agar plate method. The study evaluates the antagonistic potential of Trichoderma harzianum against the four plant pathogens by dual culture assay. The results revealed that Trichoderma harzianum was very effective in controlling the growth of Colletotrichum, partially controlled Fusarium napiforme and was compatible with Corynespora and Fusarium graminearum. The findings of this study contribute to a better understanding of T. harzianum as a sustainable and eco-friendly approach for plant diseases caused by Colletotrichum and Fusarium napiforme and their management.